SIKUEN STRATIGRAFI DAN PALEOGEOGRAFI FORMASI TALANG AKAR PADA AREA “FERCANZA”, CEKUNGAN JAWA BARAT UTARA - Fercanza, Frisdio; Gani, Reza Muhammad Ganjar; Abdurrokhim, Abdurrokhim; Muljana, Budi; Budiana, Rahmat (Fakultas Teknik Geologi Universitas Padjadjaran, 2017)
ABSTRACT“FERCANZA'' area is the working area of Pertamina Hulu Energi located in North West Java Basin. This study focused on Talang Akar formation at Arjuna sub basin. This research applies the Sequence stratigraphy concept with correlation method, which will give results in form of (1) Determination of sequences marker is more accurate, (2) Facies mapping, and (3)Sequence stratigraphy model with higher resolution detail for determination of plays, in this case stratigraphic traps on Talang Akar Formation at